ANALISIS PERBANDINGAN RISIKO BIAYA ANTARA KONTRAK LUMPSUM DENGAN KONTRAK UNIT PRICE MENGGUNAKAN METODE DECISION TREE - Oka Suputra, I Gusti Ngurah; Frederika, Ariany; Sukma Wahyuni, Putu (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 2 Juli 2008, 2012)
There are two things that always emerge from every business activity, earning profit or suffering from risk of loss, directly or indirectly, including in construction business. Many efforts have been done by contractors as the service provider, to avoid or to mitigate risk, in order to achieve the effective result. One of these is by analyzing risk in terms of the type of project contract. The selection and implementation of contract type is expected to have more positive values, although the negative effects can also come forward. The type of contract that frequently used in construction project is lumpsum and unit price contract. Thus, it is necessary to know comprehensively the advantages and disadvantages of the implementation of these two types of contract by using Decision Tree method. This method can provide comparison between lumpsump contract and unit price contract based on the value of Expected Opportunity Loss (EOL) of each contract. The value of EOL can be obtained from multiplication of probability and expectation value (NE) of every risk event that potentially causes cost-overrun. The higher of the EOL value of each risk event, the higher of the loss can be suffered. Data was retrieved from questionnaires that distributed to contractors in Gianyar Regency (32 respondents). The result of risk comparison based on types of contract related to cost aspect (as the factor of cost-overrun) showed that lumpsum contract has higher risk of loss compare to unit price contract. It can be seen from the value of EOL of this contract (80,079 %) that is higher than the other one (59,924 %).
Keywords: risiko, decision tree, Expected Opportunity Loss (EOL), Nilai Ekspektasi (NE)